Needs Analysis for the Development of a Dual Space Inquiry-Based E-Module on Momentum and Impulse Material - Zacka Hafidhon Faiz Faizal; Fuja Novitra; Hufri; Selma Riyasni (Department of Physics Universitas Negeri Padang, 2026)
The implementation of the Merdeka Curriculum emphasizes student-centered learning and supports the development of 21st-century competencies through the integration of technology in learning. In physics learning, students are expected not only to understand concepts theoretically but also to conduct scientific investigations independently. However, physics learning in schools still faces several challenges, such as teacher-centered instruction, the use of less interactive printed teaching materials, and students’ difficulties in understanding momentum and impulse concepts. Therefore, digital teaching materials that support active and inquiry-based learning are needed. This study aims to analyze the need for developing a Dual Space Inquiry-based E-Module on momentum and impulse material. This study employed the Research and Development (R&D) method using the 4-D model proposed by Thiagarajan, Semmel, and Semmel, but was limited to the Define stage. The research subjects consisted of physics teachers and senior high school students. Data were collected through document analysis, teacher interviews, and student characteristic questionnaires. The data were analyzed descriptively using qualitative and quantitative approaches. The results of the needs analysis showed that students still experience difficulties in understanding momentum and impulse concepts, physics learning is still dominated by conventional methods, and the teaching materials used have not optimally supported inquiry-based learning and technology integration. In addition, students showed interest in the use of interactive digital teaching materials in physics learning. Based on these findings, the development of a Dual Space Inquiry-based E-Module on momentum and impulse material is needed to support more interactive and meaningful physics learning.